(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
78 patients with pharyngeal tonsil hypertrophy of II-III degree aged from 18 months to 34 years were examined, who underwent endoscopic adenotomy using radio wave energy and a microshaver system under general anesthesia. In 15 patients with hypertrophy of the pharyngeal tonsil (27%), a combined surgical pathology of the upper respiratory tract was revealed, which required appropriate treatment tactics. The obtained results of treatment of adenoid vegetations indicate the high efficiency of complex surgical tactics of simultaneous correction of all intra-nasal structures based on new technologies.